Comparison of biometrics industry between Malaysia and India: an overview - Chow, Kingsley; Eng, Piew Kok; Mohan, Agan Adun Shashi; Wei, Huo So; Ahmad Dahlan, Abdul Rahman (Center for Promoting Ideas (CPI), 2011)
The amount of information being churned out by the field of biology has jumped manifold and now requires the extensive use of computers of the management of this information. The field of bioinformatics that addresses this need of biology has become an industry in its own right with the pharmaceutical and biotechnology industries being dependent on it for their growth. The bursting of the dotcom bubble in 2000 saw investors and venture capitalists flocking to the biotechnology industry in general and bioinformatics in particular. This work gives an analytical comparison of the bioinformatics industry in Malaysia and India. We examined government policy, education and economic aspects that are faced by the industry of each country. We also examined the difference in the development for the Bioinformatics industry between each country.